Edukasi Mengontrol Risiko Perilaku Kekerasan dengan Terapi Progressive Muscle Relaxation pada Penderita Resiko Perilaku Kekerasan - Mareta Akhriansyah; Raden Surahmat; Amalia Amalia; Rinda Suciarti (Universitas Baiturrahim, 2026)
Violent behavior often arises as a response to severe stress, anger, or unresolved environmental pressure, especially in patients with mental disorders that have a detrimental impact on themselves, others, and the environment. One form of non-pharmacological therapy that can be taught to clients in controlling violent behavior is using Progressive Muscle Relaxation (PMR) therapy. For this reason, the author is trying to provide a solution through community service activities in the form of the application of Progressive Muscle Relaxation (PMR) therapy to reduce angry behavior in RPK patients. The activity was carried out on Tuesday, November 9, 2024 with 30 RPK patients as participants at the Mitra Mulia Husada Foundation in Palembang. The results of the activity obtained an average pretest score of 3.8 and after the training, the average score was 10.7. This condition indicates that there is an increase in patient understanding in implementing Progressive Muscle Relaxation (PMR) therapy. Therefore, it is recommended that the Mitra Mulia Husada Foundation can apply this therapy to mental disorder patients who experience angry behavior because this therapy can be done without using special equipment and is easy to understand for patients and health workers